Domestic violence: The impact of a nature-based holistic development program on victims' well-being - Silva, A. (2018)
Several studies have highlighted the benefits of nature for human well-being. Nevertheless, the incorporation of nature as an operative resource in social support processes of vulnerable groups such as domestic violence victims is not a common practice. The complexity and prevalence of domestic violence result in a growing need for innovative intervention modalities that can contribute to provide more effective support for victims. Project CarryOn - Ecosystem services and their role in domestic violence victims' support processes was developed to address that need as a nature-based holistic program that allowed participants to benefit from direct contact with natural environments. The effectiveness of this program in promoting the participants' well-being was assessed through a mixed-methods approach, which included self-report quantitative measures (e.g., life quality, psychological adjustment, and self-esteem) and qualitative measures (e.g., women's perception of their program participation). The results showed positive changes in all dimensions, with statistically significant improvements between the pre- and post-intervention evaluations, including overall life quality and psychological adjustment. The qualitative results also reinforced other benefits derived from the nature-based program. This study highlights the importance of including nature-based activities as a complementary practice to the existing, more traditional approaches, reinforcing the role of nature as an effective resource in promoting domestic violence victims' well-being.